New names in Fallopia, Persicarioipollis, Polygonum and Reynoutria (Polygonaceae), living and fossil - Doweld, Alexander B. (Phytotaxa, 2017)
Fossil and living species of the former polyphyletic genus Polygonum s.l. are re-classified into distinct genera: Fallopia (F. conwentzii nom. nov., F. ×heterocarpa comb. nov., F. palaeodonica sp. nov., F. pliocaenica comb. nov.), Persicaria (P. asymmetrica comb. nov., P. omoloica sp. nov., P. ×pseudoincana comb. nov., P. vladichenica comb. nov., P. wolfii comb. nov., P. zablockii comb. nov.), Persicarioipollis (P. frequens comb. nov., P. persicariiformis comb. nov.), Polygonum (P. palaeosibiricum nom. nov.), and Reynoutria (R. leporimontana comb. nov., R. miosinica comb. nov., R. megalophylla comb. nov., R. trigonophylla comb. nov.). It is established that extant Polygonum ×convolvuloides Brügger is an illegitimate later homonym of P. convolvuloides Conw. and the fossil P. reticulatum P.I.Dorof. is an illegitimate later homonym of extant P. reticulatum K.Koch and P. reticulatum de Bruyn. In addition, Polygonum ×heterocarpum (≡ Fallopia ×heterocarpa comb. nov.), P. lapathiforme (≡ Persicaria lapathiformis), P. zablockii (≡ Persicaria zablockii comb. nov.) and Reynoutria paleojaponica were lectotypified.